Chemoprophylaxis vaccination with a Plasmodium liver stage autophagy mutant affords enhanced and long-lasting protection - Tejram Sahu (Nature Portfolio, 2021)
Abstract Genetically attenuated sporozoite vaccines can elicit long-lasting protection against malaria but pose risks of breakthrough infection. Chemoprophylaxis vaccination (CVac) has proven to be the most effective vaccine strategy against malaria. Here, we demonstrate that a liver stage-specific autophagy mutant of Plasmodium berghei (ATG8 overexpressor), when used as a live vaccine under a CVac regimen, provides superior long-lasting protection, in both inbred and outbred mice, as compared to WT-CVac. Uniquely, the protection elicited by this mutant is predominantly dependent on a CD8+ T-cell response through an IFN-γ-independent mechanism and is associated with a stable population of antigen-experienced CD8+ T cells. Jointly, our findings support the exploitation of liver-stage mutants as vaccines under a CVac protocol. This vaccination strategy is also a powerful model to study the mechanisms of protective immunity and discover new protective antigens.